2019 novel coronavirus disease (COVID‐19) in patients with inflammatory bowel diseases. Issue 2 (7th June 2020) - Taxonera, Carlos; Sagastagoitia, Iñigo; Alba, Cristina; Mañas, Norberto; Olivares, David; Rey, Enrique
Summary: Background: Data on patients with inflammatory bowel diseases (IBD) who have had 2019 novel coronavirus (SARS‐CoV‐2) disease (COVID‐19) are needed. Aims: To report the clinical characteristics, including gastrointestinal symptoms, of COVID‐19 in IBD patients, and to assess the risk of COVID‐19 in IBD. Methods: This case series included consecutive IBD patients with laboratory‐confirmed COVID‐19. Age‐adjusted cumulative incidences were compared with the general population in the Madrid region. Results: Through April 8, 12 of 1918 IBD patients were diagnosed with COVID‐19. The average age was 52 years, 75% of the patients were female and 58.3% had Crohn's disease. Seven patients (58%) were on maintenance treatment with immunomodulators/biologics, of these four with combined therapy (33%). Eight patients (66%) required hospitalisation (one intensive care unit admission, and two deaths), and four patients were isolated at home. Nine patients had diarrhoea ranging between 4 and 10 loose stools per day (mean 5.4, SD 1.6). In five patients (42%) diarrhoea was a presenting symptom. In two patients, diarrhoea was the only symptom at debut. Cumulative incidence of COVID‐19 was 6.2 per 1000 IBD patients. IBD patients had a lower adjusted incidence ratio of COVID‐19 (OR 0.74, 95% CI 0.70‐0.77; P  < 0.001), and a similar associated mortality ratio (OR 0.95, 95% CI: 0.84‐1.06; P  = 0.36), compared with the general population. Conclusions: IBD patients do not have an increased risk of COVID‐19 and associated mortality compared with the general population. In many IBD patients, diarrhoea was a presenting symptom, and sometimes, was the only symptom at onset of COVID‐19.